Numerical Simulation of ChlorideI on Ingression in Mortar incorporating the Effect of ITZ using an integrated COMSOL-IPHREEQC Framework - Krishnya, S.; Elakneswaran, Y.; Yoda, Y.; Kitagaki, R. (Springer, 2023)
Thepredictionofchlorideingressionincement-basedmaterialhas gainedagreatdealofinterestamongresearchersasitcauseslong-termstructuraldamageinbuildingsbychloride-inducedreinforcementcorrosion.TheCl− diffusioninmortarisinfluencedbyinternalfactorsincludingpore-structureand hydrateswhicharedeterminedbyclinkerproperties,mixturerecipe,andcuring conditionsandexposureconditions.TheCl−penetrationinmortarleadstothe modificationofthemicrostructureandpore-solutionduetothedisequilibriumof thehydrates-poresolutionsystem.Consideringthecomplexityoftheprocessby incorporatingallaforementionedfactorsandinteractionofCl−withhydrates, anewmodelishereinproposedforpredictingthemicrostructureofthemortar duringtheCl−diffusion.Inthiswork,themicrostructureofmortarisconsideredasathree-phasematerial:aggregates,interfacialtransitionzone(ITZ)and bulkpaste,andITZisrealisticallyconsideredashighW/Cpastecomparedto theinitialW/C.ThedevelopedCOMSOL-IPHREEQCmodelinvolveshydration modelforcalculatingthedissolutionofclinkerinbulkpasteandITZ,thermodynamicmodelincludingthesurfacecomplexationmodeltopredictthehydrates andtheCl−adsorptionbyhydrates,homogenizationapproachtocomputethe averagehydrates,porosity,poresolutioncompositionanddiffusionparametersof themortarandCOMSOLMultiphysicstoperformthetransportationcalculation. Thepredictedresultsarevalidatedwithexperimentalresultsavailableintheliteraturestoverifythereliabilityoftheproposedmodel.TheeffectofITZonthe penetrationofCl−isalsoassessedinthiswork.
Keywords: Chloride ion diffusion; Hydration products; Interfacial transition zone; Porosity; COMSOL-IPHREEQC